From subsistence to market economy: Responses of Tibetan pastoralists to new economic realities - Manderscheid, Angela; Naukkarinen, Arvo; Ning, Wu; Colpaert, Alfred (Rangifer, 2004)
In many regions around the world the pastoral economy shifted from subsistence-oriented to a market-oriented production. Pastoral goods acquired monetary value and became a market commodity that entailed changes in the production system and in the attitude towards livestock. On the Tibetan plateau this shift did not follow a linear way. Until the 1950s, most consumption requirements could be satisfied with animal products. Economic exchange relations were essential to provide grain requirements, at least for those households who relied exclusively on animal husbandry. During the Mao era, animal husbandry was carried out in line with state targets and the produce was delivered according to central planning. In the late 1970s the transition towards a market-oriented production began. This paper discusses the recent reactions of pastoralists to the new realities in one specific area on the eastern Tibetan plateau. This shift from pastoral products to market commodities, the commercial network established as well as the market places for pastoral produce, are examined in this paper. These facts show that the pastoralists in question successfully market their produce. The research area, Dzoge county, is located on the eastern border area of the Tibetan plateau, where different ethnic groups live in proximity to each other. Grassland predominates the landscape, used by nomads as pastures for livestock breeding (yak, sheep and horses). Mobile animal husbandry and the marketing of the livestock products are decisive to guarantee the livelihood of the majority of the population.